Posttranscriptional regulation of 14‐3‐3ζ by RNA‐binding protein HuR modulating intestinal epithelial restitution after wounding - Hansraj, Natasha Z. (Physiol Rep, 2016)
The 14‐3‐3ζ is a member of the family of 14‐3‐3 proteins and participates in many aspects of cellular processes, but its regulation and involvement in gut mucosal homeostasis remain unknown. Here, we report that 14‐3‐3ζ expression is tightly regulated at the posttranscription level by RNA‐binding protein HuR and plays an important role in early intestinal epithelial restitution after wounding. The 14‐3‐3ζ was highly expressed in the mucosa of gastrointestinal tract and in cultured intestinal epithelial cells (IECs). The 3′ untranslated region (UTR) of the 14‐3‐3ζ mRNA was bound to HuR, and this association enhanced 14‐3‐3ζ translation without effect on its mRNA content. Conditional target deletion of HuR in IECs decreased the level of 14‐3‐3ζ protein in the intestinal mucosa. Silencing 14‐3‐3ζ by transfection with specific siRNA targeting the 14‐3‐3ζ mRNA suppressed intestinal epithelial restitution as indicated by a decrease in IEC migration after wounding, whereas ectopic overexpression of the wild‐type 14‐3‐3ζ promoted cell migration. These results indicate that HuR induces 14‐3‐3ζ translation via interaction with its 3′ UTR and that 14‐3‐3ζ is necessary for stimulation of IEC migration after wounding.